The Planar Si(IV) of Bis(catecholato)silane on a Metal Surface Induced by a Surface Constraint - Liu, Peizhen; Zhang, Tiantong; Zhang, Jinyu; Wang, Peichao; Wang, Hongchao; Han, You; Zhao, Dongbing; Gao, Hong-Ying (Journal of physical chemistry. C, 2025)
The structure of bis(catecholato)silane has been subject to debate, as to whether it is its tetrahedral or planar Si(IV). To tackle the discussion, here, the bis(catecholato)silane molecules with visible molecular-level images on different metal surfaces are investigated by scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT) simulations. It is found that the bis(catecholato)silane shows a tetrahedral Si(IV) structure on both Au(111) and Ag(111) surfaces, while the bis(catecholato)silane can show a nearly planar Si(IV) structure on the Cu(111) surface due to the strong interaction between the SiO4 moiety and the metal surface. Naturally, the conformational difference results in the self-assembly and on-surface chemistry behaving differently. Furthermore, the coverage of bis(catecholato)silane influences the self-assembly structures, indicating that the interactions among organic molecules affect the molecular tetrahedral or planar conformations. Our study reveals fundamental knowledge of the bis(catecholato)silane molecules on a surface, especially the tetrahedral or planar Si(IV) selectivity influenced by the surface constraint.